Using co-design to reduce Pacific health inequity: the example of NIU, a model to improve gout management. - Ofanoa, Malakai; Tu'akoi, Siobhan; Ofanoa, Samuela; Goodyear-Smith, Felicity (Journal of Primary Health Care, 2025)
The article focuses on the use of a co-design approach to address health inequities related to gout management among Pacific peoples in Aotearoa New Zealand. It highlights the development of the NIU model, which aims to improve the uptake of urate-lowering therapy (ULT) for gout, a condition that disproportionately affects Pacific communities. The model was created through collaboration between the Pacific Peoples Health Advisory Group and the Pacific Practice-Based Research Network, emphasizing community involvement and cultural relevance in health interventions. The NIU model symbolizes resilience and collective effort, aiming to enhance health outcomes and reduce disparities in gout management among Pacific populations.